The Influence of Social Media Marketing Activities on Customer Loyalty A Study of the E-commerce Industry - Dede Haikal Fahmi Mubarok; Adi Setiawan (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
The swift expansion of e-commerce in the digital age has encouraged businesses utilize social media as a primary marketing tool to build customer loyalty. This paper is intended to analyze the influence of social media marketing activities (SMMA) on customer loyalty by using Customer Equity Drivers—comprising value equity, brand equity, and relationship equity—as mediating variables. This investigation utilizes a quantitative technique with an explanatory design. The study gathered data via questionnaires from 65 active e-commerce users in Cirebon City using accidental sampling. Data analysis utilized path analysis in order to examine the relationships occurring directly and indirectly considering the Stimulus–Organism–Response(SOR) models. The outcomes reveal that SMMA contribute positively to Customer Equity Drivers, and all dimensions significantly influence customer loyalty. These findings indicate that Customer Equity Drivers act as mediators in the relationship between social media marketing activities and customer loyalty.